Flux modulated rotating pole piece magnetic gear - Mohd Firdaus M. A Halim; E. Sulaiman; R. N. F. K. R. Othman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this paper, the CMG is re-condition so that the pole piece act as the outer rotor instead of surface mount PM. This magnetic coupling of the CMG is similar to the conventional CMG which uses harmonic to transfer the torque and speed from the inner rotor to the outer rotor. The working principle of the proposed CMG is derived analytically and simulated using finite element software. For this recondition, the PM at the outer section become stationary hence, retaining sleeve can be removing. The proposed MG produced 18% higher average torque than the conventional MG with drawback in torque ripple. The proposed CMG also produce higher gear ratio than the same pole pair of conventional CMG.